Wireless Water Level Monitoring System - Irawan Wibowo (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2017)
The use of sensors that suit the needs of the system affects the water pump. By using water buoys and infrared we can automate the water pump, but the chances are that it will be processed very little as it fixates on the upper and lower limits. If using electric wire working principles, it is possible to control the water pump more in accordance with the number of wires in use but that is not practical when changes occur and the addition of water level. Therefore, although a bit expensive use of ultrasonic sensors to be a more appropriate choice because the resulting data in the form of analog data making it easier to control the many possibilities of water pump work and also make it easier to process the data in the form of graphs. Display to the user is needed if the user wants to know how high the water level. In addition to remote monitoring via the internet, there is an LCD display for easy supervision when at home.